Assessment of Geriatric Patients with a Diagnosis of Acute Surgical Abdomen: A Prospective Study - Mashallah, Dina Ismail; Husam Saleh Shnawa; Zeinab Abdulrahman Yahya (Open Journal of Physicians and Surgeons, 2026)
Background: Acute abdomen is one of the most common medical conditions among surgical diseases. Acute abdominal processes were described in ancient texts dating back to the time of Hippocrates; however, it was not until the end of the last century that John B. Deaver introduced the term "acute abdomen" into medical literature. Objective: To assess the demographic criteria of geriatric patients diagnosed with acute surgical abdomen. Patients and method: A descriptive longitudinal cross-sectional observational study was conducted at our hospital included elderly patients (>60 years old) who diagnosed with surgical acute abdomen, in the period from the first of January-to the end of Dec. 2025. Results: 395 patients with a diagnosis of acute surgical abdomen were studied, of which 56 (14.17%) correspond to older adults, Twenty-five correspond to males (44.64%) while females represent 31 patients (55.36%), the average age for both sexes was 71.72±5.5 years, the intestinal obstruction (46.4%)were the most common causes of acute surgical abdomen then stuck or strangulated hernias (12.5%), Twenty patients (35.7%) had some complication and 13 patients (23.21%) presented 2 or more complications, the most frequent were sepsis in 17.85% of patients, renal failure (14.28%), septic shock (10.7%), 25 patients (44.64%) remained hospitalized for 3 days or less, 22 (39.29%) from 4 to 7 days and 9 (16.07%) greater than 8 days, evidencing that the majority of patients (55.36%) remained hospitalized for more than 4 days, including the majority with medical complications (90%), two complicated patients died in the mid-postoperative period. The period of hospitalization varied from 1 to 30 days, with an average of 6.2 days. Conclusion: We observe in our environment great morbidity in these patients that could be prevented by being treated at earlier stages, for example, digestive cancer and complicated hernias.